PENGANGGURAN TERBUKA DAN DETERMINANNYA DI INDONESIA TAHUN 2013-2017 - Apsari Demmy Salsabella; Wahyu Hidayat; Hendra Kusuma (Jurnal Ilmu Ekonomi JIE, 2020)
The level of open unemployment is the percentage of unemployment to the total labor force. The purpose of this study was to analyze the effect of population, GRDP, and education level on the level of open acquisition in Indonesia in 2013-2017. The type of data used in this study is secondary data, data collection in this study uses multiple linear regression methods. The data used consists of panel data. The population has a negative and significant effect, while the GRDP has a positive and significant effect, and the level of education has a positive and significant effect on the level of open acquisition.